Natural Killer Cells: A Coherent Model for Their Functional Role in Mycobacterium tuberculosis Infection - Esin, Semih (J Innate Immun, 2014)
Tuberculosis is still a leading cause of bacterial infection worldwide, with an estimate of over two billion people latently infected with Mycobacterium tuberculosis (MTB). A delicate interplay between MTB and the host's innate and acquired immune system can influence the outcome of the infection, which ranges from pathogen elimination to the establishment of a latent infection or a progressive disease. Although the host cell-mediated adaptive immune response is of vital importance in the control of MTB infection, growing evidence indicates that innate immune cells may greatly influence the outcome of the interaction between the bacterium and the host. Among the cell populations likely to play a role in the host immune response to MTB, natural killer (NK) cells have recently attracted considerable interest. This review is dedicated to dissecting the role of NK cells in immunity to tuberculosis, reporting the most relevant findings and providing a working model of the possible contribution of NK cells in early and late events associated with MTB infection.